INTERNATIONAL RELATIONS PERSPECTIVE OF SISTER CITY: CONCEPT AND PRACTICES - Putra, Reynaldi Mandala; Rachman, Junita Budi; Dermawan, Windy (Natapraja, 2021)
International relations is a study that discusses the relationship between actors in the international world. In its development, international relations are no longer dominated by the state as the main actor. International relations developed and expanded so that other actors, such as sub-national actors, emerged. Sub-national actors can include local or regional governments, one of which is the city government. Sister city is one form of international relations carried out by City Government actors. This paper will explain the concept and practice of sister city in International Relations. The concepts/theories used are International Relations and Sister city. While the research method used is descriptive qualitative by using the result of interviews, books, journals, websites and others as a reference. Conceptually, a sister city is a cooperative relationship carried out by two or more City Governments based on their similarities. However, in the practice, based on case studies, the reasons for sister city relationships are not always based on similarities. The practice of sister city relations has been carried out by many cities in the world in various fields. Sister cities also tend to be intertwined for a long time, but not a few have not been implemented effectively or even not running at all.